2022
DOI: 10.3389/fbioe.2022.991676
|View full text |Cite
|
Sign up to set email alerts
|

Digital chain for pelvic tumor resection with 3D-printed surgical cutting guides

Abstract: Surgical cutting guides are 3D-printed customized tools that help surgeons during complex surgeries. However, there does not seem to be any set methodology for designing these patient-specific instruments. Recent publications using pelvic surgical guides showed various designs with no clearly classified or standardized features. We, thus, developed a systematic digital chain for processing multimodal medical images (CT and MRI), designing customized surgical cutting guides, and manufacturing them using additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Similar results stating the superiority of PSI in terms of shorter surgical time compared to SN in pelvis were presented by Gouin et al [31] , reporting a maximum of 5 min time needed for PSI guide positioning [31] . 14 min was instead the time reported by Fujiwara et al for SN intraoperative use, again far more than the 60–92 s reported by Biscaccianti et al for PSI use [46] . On the other side, Evrard et al reported no difference in intraoperative time between PSI and free hand technique [34] .…”
Section: Resultsmentioning
confidence: 66%
“…Similar results stating the superiority of PSI in terms of shorter surgical time compared to SN in pelvis were presented by Gouin et al [31] , reporting a maximum of 5 min time needed for PSI guide positioning [31] . 14 min was instead the time reported by Fujiwara et al for SN intraoperative use, again far more than the 60–92 s reported by Biscaccianti et al for PSI use [46] . On the other side, Evrard et al reported no difference in intraoperative time between PSI and free hand technique [34] .…”
Section: Resultsmentioning
confidence: 66%
“…Using Digital Imaging and Communication in Medicine approaches (DICOM), the 3D images of tumors with normal anatomy are reconstructed using segmented thin-slice computed tomography (CT) and magnetic resonance imaging (MRI) [ 11 ]. The reconstructed anatomical 3D images of bony tissues and tumors are then exported as a series of polygons, the number of which directly correlates with the resolution in the standard triangulation language format [ 12 ].…”
Section: Digital Imaging Applications For Surgical Interventionsmentioning
confidence: 99%
“…One of the most important advantages of PSGs is the achievement of an accurate resection of bone tumors with safe margins [ 11 , 18 , 19 ]. From previous cadaver studies, manual resection can result in inaccuracies of up to 5–15 mm, which might lead to unexpected intralesional resection [ 20 , 21 , 22 , 23 ].…”
Section: 3d-printing Technique For Surgical Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive manufacturing technology has demonstrated unparalleled superiority in pelvic tumor surgery due to its personalization, high-precision, and rapidly accessible manufacturing ( Chen et al, 2016 ). Preoperative surgical planning, intraoperative guides for precise osteotomy planes, and implant reconstruction with 3D printed prostheses have led to the increasing application of additive manufacturing technology in pelvic tumor surgery ( Biscaccianti et al, 2022 ).…”
Section: Pelvic Tumormentioning
confidence: 99%